Persuasiveness as a basic element of media discourse - Rybka, Kseniya V. (Journal of the Belarusian State University. Journalism, 2021)
The category of persuasiveness of media discourse is considered.Various interpretations of the term «persuasiveness» are presented, a description of the category is given, persuasive strategies and techniques are analysed. The question is raise about the power of the influence of the media: the proven influence of the media on consciousness, although great, has its limitations. In particular, due to the peculiarities of the human psyche, the recipient of information is inclined to assimilate only those messages that harmoniously fit into the subjective reality of the addressee. Changing audience attitudes is a long term process, in which persuasiveness can be an effective tool. The category of persuasiveness is described as a universal strategy of mass media discourse, which, due to the argumentation basis and elements of affective influence, is the most effective way to achieve perlocutionary effect.